Progress towards developing dual-purpose icanltivars of pearl millet (Pe~nis@tugmla ucum) in India - YADAV, O P; KHAIRWAL, I S (The Indian Journal of Agricultural Sciences, 2011)
An experiment was carried out during 2003 for assessing the genotypic variation in the most recently developed pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stuntz] experimental cultivars for stover and grain productivity. A total of 62 cultivars, including 43 hybrids and 19 composites were grown at 31 locations (21 locations for hybrids and 10 locations for composites). The stover productivity was significantly influenced by cultivar maturity though this relationship was stronger in composites (r = 0.73** P < 0.01) than in hybrids (r = 0.52** P < 0.01). There existed a wide range in productivity for grain and stover yields in the two groups of cultivars with mean performance of hybrids in the multilocation trials being 36% higher for grain yield and 19% higher for stover yield than composites. There were no trade-off effects between grain yield and stover yield in the recently developed cultivars. Considerable scope exists for the selection of genotypes with higher stover yield without sacrificing grain yield or vice-versa depending upon the requirements of different mixed farming systems.